Pengobatan malaria secara rasional - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK Several drugs are currently used for malaria prophylaxis. No single drug, however, is a completely effective prophylactic against all species and strains of human malaria parasites, or against all stages in the parasite life cycle. Chloroquine is the drug of choice for prophylaxis against alt forms of malaria parasites except for chloroquine resistant falciparum malaria. In this case it is necessary to give chloroquine combined with an additional drug, e.g., Maloprim, Fansidar. The treatment of malaria should be based on the cause, the severity of illness and the posibility of drug resistance. For all species except chloroquine resistant faksparum should be given chloroquine combined with primaquine. Quinine and Fansidar/ Maloprim in a combination is recommended against chloroquine resistant fakiparum. Severefalciparum malaria must be thought as emergency case, for these case intra venous quinine should be given rapidly followed by parasite counts and haematological monitoring without delay the patient has cerebral malaria.